5v-41=-6(v-6)

Simple and best practice solution for 5v-41=-6(v-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5v-41=-6(v-6) equation:


Simplifying
5v + -41 = -6(v + -6)

Reorder the terms:
-41 + 5v = -6(v + -6)

Reorder the terms:
-41 + 5v = -6(-6 + v)
-41 + 5v = (-6 * -6 + v * -6)
-41 + 5v = (36 + -6v)

Solving
-41 + 5v = 36 + -6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '6v' to each side of the equation.
-41 + 5v + 6v = 36 + -6v + 6v

Combine like terms: 5v + 6v = 11v
-41 + 11v = 36 + -6v + 6v

Combine like terms: -6v + 6v = 0
-41 + 11v = 36 + 0
-41 + 11v = 36

Add '41' to each side of the equation.
-41 + 41 + 11v = 36 + 41

Combine like terms: -41 + 41 = 0
0 + 11v = 36 + 41
11v = 36 + 41

Combine like terms: 36 + 41 = 77
11v = 77

Divide each side by '11'.
v = 7

Simplifying
v = 7

See similar equations:

| 2m+12=-31 | | -2+2x=4+12x | | Y=-4x+340 | | 2x^2-5x-21=p | | 3b-3(-23+2b)=48 | | 5(x-3)-x= | | Tanx-cotx=0 | | 22=-3+5u | | 2(7p+8)+6(2p+8)= | | 10-5x-10x+4= | | 4c+30=4c+20 | | c/6+2=-1 | | 2x+1=11x-28 | | 5(3-x)-2(6-5x)=33 | | 7(2)-6(-1)= | | 7(-5)-6(-3)= | | (3x+1)+(x+12)= | | 12-2j=4 | | 49x^2+101x=-67 | | -16=-4u+2(u-5) | | 7(7)-6(5)= | | 49x^2+101x+67=0 | | 7(-4)-6(0)= | | 5(3c-2)=40-2c | | 8+41nx=3 | | -33=-7(2)-3 | | b-2.25=1 | | 3(-4x-4)=5+1x | | 9(3)+2(-7)= | | 9(0)+2(-8)= | | 2y+(y-3)+3=7y-(2y+4) | | 5x+17=4(3x+1) |

Equations solver categories